Online "curriculum" of Jihad: four broad themes - Muhammad Haniff Hassan (2016)
There are four broad themes that can be found from the jihadist’s online ideological materials to elicit support and indoctrinate symphathisers and subsequently transform them into recruits or freelance radicals. Some practical ideas for counter-ideological work can however also be extracted from them.